The Link Between Obesity and Periodontal Disease: A Narrative Review - Renu S. Samson; Kurian Punnoose; Meenakshi A. Archana; Manojkumar Sachidanandan; Mohammed S. Alshammari; Tayf N. Alshammari; Babu J. Suresh; C. Swarnalatha; Abhishek S. Nayyar (International Journal of Medicine and Health Development)
Obesity is a chronic disease with a global spread. The increasing worldwide prevalence of this condition is becoming a considerable cause of concern due to its negative impact on the quality of life of the affected individuals, rising morbidity and mortality, and the overall growing cost of healthcare options. A narrative review was conducted using literature identified through searches of PubMed, DOAJ, Scopus, Google Scholar, and relevant reference lists, focusing on articles published. The World Health Organization has declared obesity as a predisposing risk factor to a plethora of general and oral health conditions that may range from an increased cardiovascular risk to a variety of general body cancers. In a similar context, though, the relationship between obesity and periodontal disease needs further investigation, the present review attempts to cover this rarely discussed subject highlighting the conclusions of the studies conducted and the previous work done in the literature on this aspect.